2014
DOI: 10.5152/ucd.2014.2753
|View full text |Cite
|
Sign up to set email alerts
|

The retrospective documentation of legal cases with bile duct injury that were submitted for consideration to İstanbul Forensic Medicine Institute by the courts between 2008-2012

Abstract: Statistical AnalysisThe rates and distributions in this case series were indicated as percentages and frequencies. RESULTSThe physicians were found to be faulty in all the cases that were examined. The reason for physician fault was failure to show the necessary professional care and attention in one (4.7%) file, whereas the Objective: The aim was to evaluate the parameters that were considered by Forensic Medicine in bile duct injury as well as the issues that the physicians were found to be faulty. Material … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…After the titles and abstracts were screened for relevance, 22 remaining articles were further assessed for eligibility, and 8 were excluded. The 14 studies, whose characteristics are reported in Table 1, are included in this scoping review [17,[24][25][26][27][28][29][30][31][32][33][34][35]; the reasons of exclusion of the 8 studies are reported in Figure 1 [36][37][38][39][40][41][42][43]. In the 14 studies, 2406 patients were enrolled.…”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…After the titles and abstracts were screened for relevance, 22 remaining articles were further assessed for eligibility, and 8 were excluded. The 14 studies, whose characteristics are reported in Table 1, are included in this scoping review [17,[24][25][26][27][28][29][30][31][32][33][34][35]; the reasons of exclusion of the 8 studies are reported in Figure 1 [36][37][38][39][40][41][42][43]. In the 14 studies, 2406 patients were enrolled.…”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
“…However, domain 6 was particularly heterogeneous for the no information reported or different methods used to assess outcomes in different intervention groups. Nine out of fourteen studies were assessed as "moderate" risk of overall bias [5,17,[24][25][26]28,29,32,35], while two were determined to have a "serious" risk [27,31], and three a "critical" risk [30,33,34]. Regarding the bias due to confounding, nine out of fourteen studies were evaluated as having a "moderate" risk [5,17,[24][25][26]28,29,32,35]; differently this risk was higher as "serious" in studies performed through insurance surveys or databases [31,34], or "critical" in single team experiences [30,34] or Justice Court [27].…”
Section: Quality Assessment Of Studiesmentioning
confidence: 99%
“…Karakaya et al, in their 2014 study, examined 21 cases assessed by the Institution of Forensic Medicine due to bile duct injury after laparoscopic cholecystectomy from 2008 to 2012, finding that all cases of injury were due to surgical inadequacies in cholecystectomy. While the reason for the inadequacies was regarded as “late recognition of bile duct injury and delayed transfer of the patient” in 20 cases (95.3%), it was “failure to provide necessary professional care and attention” in the remaining 1 case (4.7%) [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 10 ] The files of 23 legal cases with BDI that were referred by the Turkish courts to the Istanbul Forensic Medicine Institute for expert opinion were analysed — late recognition of injury and late transfer of patient (to a higher centre) was found in 20 (45%) files. [ 11 ] Immediate non-specialist repair is also an independent predictor for possible litigation. [ 12 ] In Germany, four out of 44 cases where BDI was recognized intraoperatively and immediate repair was performed by a biliary surgeon were not considered as malpractice.…”
mentioning
confidence: 99%